Cu Intercalation and Br Doping to Thermoelectric SnSe2 Lead to Ultrahigh Electron Mobility and Temperature‐Independent Power Factor. (1st December 2019) - Zhou, Chongjian; Yu, Yuan; Zhang, Xiangzhao; Cheng, Yudong; Xu, Jingtao; Lee, Yong Kyu; Yoo, Byeongjun; Cojocaru‐Mirédin, Oana; Liu, Guiwu; Cho, Sung‐Pyo; Wuttig, Matthias; Hyeon, Taeghwan; et al.
Abstract: Due to its single conduction band nature, it is highly challenging to enhance the power factor of SnSe2 by band convergence. Here, it is reported that simultaneous Cu intercalation and Br doping induce strong Cu–Br interaction to connect SnSe2 layers, otherwise isolated, via "electrical bridges." Atom probe tomography analysis confirms a strong attraction between Cu intercalants and Br dopants in the SnSe2 lattice. Density functional theory calculations reveal that this interaction delocalizes electrons confined around SnSe covalent bonds and enhances charge transfer across the SnSe2 slabs. These effects dramatically increase electron mobility and concentration. Polycrystalline SnCu0.005 Se1.98 Br0.02 shows even higher electron mobility than pristine SnSe2 single crystal and the theoretical expectation. This results in significantly improved electrical conductivity without reducing effective mass and Seebeck coefficient, thereby leading to the highest power factor of ≈12 µW cm −1 K −2 to date for polycrystalline SnSe2 and SnSe. It even surpasses the value for the state‐of‐the‐art n‐type SnSe0.985 Br0.015 single crystal at elevated temperatures. Surprisingly, the achieved power factor is nearly independent of temperature ranging from 300 to 773 K. The engineering thermoelectric figure of merit ZTeng for SnCu0.005 Se1.98 Br0.02 is ≈0.25 between 773 and 300 K, the highest ZTeng ever reported for any form of SnSe2 ‐based thermoelectric materials. Abstract : A new strategy for enhancing thermoelectric performance for eco‐friendly SnSe2 is demonstrated. Simultaneous Cu intercalation into a van der Waals gap and Br doping into a SnSe2 lattice electrically bridges otherwise isolated SnSe2 layers, leading to a record high electron mobility, power factor, and engineering ZT for SnSe2 . Its highly unusual temperature‐independent power factor is crucially important in stable thermoelectric power generation.